Kajian Risiko Bencana Alam Pada Tower SUTT 150 kV Bandung Timur – Ujung Berung - Setiawan, Deni; Sitompul, Steven Hotmartua (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2025)
Infrastructure—such as transportation, telecommunications, sanitation, and energy—forms the backbone of a country’s economic development. Within infrastructure projects, risk management plays a critical role in mitigating potential losses. One such system is the High Voltage Air Duct (SUTT), which distributes electricity from power plants—typically located far from urban centers—to end users. The 150kV East Bandung–Ujung Berung SUTT project involves 26 transmission towers supplying electricity from East Bandung to Ujung Berung. This study aims to identify natural disaster risks that may impact the 150kV SUTT towers in this project. The research was conducted on-site along the East Bandung–Ujung Berung transmission corridor. Using a qualitative approach and the AS/NZS 4360 risk management framework, natural disaster risks were mapped and analyzed. Findings indicate that earthquakes pose the most significant natural disaster risk to the 26 SUTT towers. The highest-ranked risk factor identified is the potential for tower foundations to collapse or shift due to seismic activity, which could lead to severe structural damage. This risk scored 18.32, placing it in the “very high” category. Another major risk is delayed emergency maintenance following a natural disaster, which can result in further deterioration and significantly reduce the towers’ service life. This risk scored 15.05, classified as “high”.